Comparing Relations: Whakapapa and Genealogical Method - Salmond, Amiria J.M. (Waka Kuaka, 2019)
While relational thinking is currently in vogue across the academy, the relations scholars have in mind are often of a certain kind. As anthropologist Marilyn Strathern observes, the idea of relations as connections has a distinct pedigree, one that can work to obscure different (kinds of) relations within and among different (kinds of) things. Here I discuss some implications of these insights by setting them alongside relational methodologies developed in early twentieth-century Aotearoa New Zealand by the statesman and scholar Sir Apirana Ngata. Ngata’s mobilisation of anthropology in the service of an ambitious program of Māori artistic, cultural and economic revitalisation serves as a powerful precedent for rethinking and reworking relations through ethnography in theory as well as in practice. His advancement of ethnographic methods that deliberately mobilised perspectives constituted by whakapapa ‘Māori relatedness’ is brought into relation with recent discussions about anthropological methods and politics. In particular, whereas critics of some “post-relational” approaches diagnose a lack of both political traction and practical application in these efforts to investigate different modes of relatedness, Ngata’s example points to such experiments’ potential to help challenge and materially transform institutional and popular conceptions, as well as the day-to-day living conditions of marginalised peoples.